Variations of physical activity and sedentary behavior between before and after cancer diagnosis: Results from the prospective population-based NutriNet-Santé cohort. Issue 40 (October 2016) - Fassier, Philippine; Zelek, Laurent; Partula, Valentin; Srour, Bernard; Bachmann, Patrick; Touillaud, Marina; Druesne-Pecollo, Nathalie; Galan, Pilar; Cohen, Patrice; Hoarau, Hélène; Latino-Martel, Paule; Menai, Mehdi; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Physical activity (PA) but also reduced sedentary behavior may be associated with better prognosis and lower risk of recurrence in cancer patients. Our aim was to quantify the variations in PA and time spent sedentary between before and after diagnosis, relying on prospective data in French adults. We also investigated sociodemographic and lifestyle factors associated with these variations. Subjects (n = 942) were incident cancer cases diagnosed in the NutriNet-Santé cohort between 2009 and 2015. PA and sedentary behavior were prospectively collected with the 7-day short version of the IPAQ questionnaire every year since subjects' inclusion (i.e., an average of 2 year before diagnosis). All PA and sitting time points before and after diagnosis was compared by mixed model. Factors associated with decrease in PA and increase in sitting time were investigated using logistic regressions. Overall and vigorous PA decreased after diagnosis ( P  = 0.006, −32.8 ± 36.8 MET-hour/week on average, in those who decreased their overall PA and P  = 0.005, −21.1 ± 36.8 MET-hour/week for vigorous PA, respectively), especially in prostate (−39.5 ± 36.3 MET-hour/week) and skin (−35.9 ± 38 MET-hour/week) cancers, in men (−40.8 ± 46.3MET-hour/week), and in those professionally inactive (−34.2 ± 37.1 MET-hour/week) (all P  < 0.05). Patients with higher PA level before diagnosis were more likely to decrease their PA (odds ratio [OR]: 4.67 [3.21–6.81], P  < 0.0001). Overweight patients more likely to decrease moderate PA (OR: 1.45 [1.11–1.89], P  = 0.006) and walking (OR: 1.30 [1.10–1.70], P  = 0.04). Sitting time increased ( P  = 0.02, +2.44 ± 2.43 hour/day on average, in those who increased their sitting time), especially in women (+2.48 ± 2.48 hour/day), older patients (+2.48 ± 2.57 hour/day), and those professionally inactive (2.41 ± 2.40 hour/day) (all P  < 0.05). Patients less sedentary before diagnosis were more likely to increase their sitting time (OR: 3.29 [2.45–4.42], P  < 0.0001). This large prospective study suggests that cancer diagnosis is a key period for change in PA and sedentary behavior. It provides insights to target the subgroups of patients who are at higher risk of decreasing PA and increasing sedentary behavior after cancer diagnosis.